Micro data and macro technology - Ezra Oberfield; Devesh Raval (Federal Reserve Bank of Chicago, 2012)
We study the implications of microeconomic heterogeneity for aggregate technology, showing that the aggregate elasticity of substitution between capital and labor can be expressed as a simple function of plant level structural parameters and sufficient statistics for plant heterogeneity. This allows for a new approach to estimating the aggregate elasticity using microeconomic data and allows us to examine how the aggregate elasticity varies over time or across countries. We then use plant level data from the Census of Manufactures to construct an aggregate elasticity of substitution for the manufacturing sector, and estimate an aggregate elasticity of approximately 0.72 in 1987. We find that the aggregate elasticity has risen over time in the US and is higher in less developed countries. These differences are quantitatively important; our estimates imply that a change in the interest rate has a 50 percent larger impact on India than the US. Finally, we measure the bias of aggregate technical change using our estimates of the aggregate elasticity, and find that the bias of technical change has increased in recent years.
Keywords: 330; Elasticity of Substitution; Aggregation; Bias of Technical Change